Podcast
Questions and Answers
Given $f(x) = 7x^3 - 4x + 5$, what is $f'(x)$?
Given $f(x) = 7x^3 - 4x + 5$, what is $f'(x)$?
- $21x^2 - 4$ (correct)
- $21x^2 - 4x$
- $21x^3 - 4$
- $21x^2 - 4x + 5$
If $f(x) = \frac{1}{x^3}$, find $f'(x)$.
If $f(x) = \frac{1}{x^3}$, find $f'(x)$.
- $-\frac{1}{3x^2}$
- $\frac{1}{x^4}$
- $\frac{3}{x^2}$
- $\frac{-3}{x^4}$ (correct)
Determine the derivative of $f(x) = x^2 \cdot cos(x)$.
Determine the derivative of $f(x) = x^2 \cdot cos(x)$.
- $2x \cdot cos(x) + x^2 \cdot sin(x)$
- $2x \cdot sin(x) + x^2 \cdot cos(x)$
- $2x - sin(x)$
- $2x \cdot cos(x) - x^2 \cdot sin(x)$ (correct)
Find the derivative of $f(x) = \sqrt[5]{x^2}$.
Find the derivative of $f(x) = \sqrt[5]{x^2}$.
What is the derivative of $f(x) = \frac{x^2 + 1}{x}$?
What is the derivative of $f(x) = \frac{x^2 + 1}{x}$?
Find the derivative of $f(x) = (x^2 + 3)(2x - 1)$.
Find the derivative of $f(x) = (x^2 + 3)(2x - 1)$.
Determine the derivative of $f(x) = tan(x) \cdot cos(x)$.
Determine the derivative of $f(x) = tan(x) \cdot cos(x)$.
What is the slope of the tangent line to the curve $f(x) = x^3 - 2x^2 + x$ at $x = 2$?
What is the slope of the tangent line to the curve $f(x) = x^3 - 2x^2 + x$ at $x = 2$?
If $f(x) = \frac{5x}{x^2 + 1}$, find $f'(x)$.
If $f(x) = \frac{5x}{x^2 + 1}$, find $f'(x)$.
Given $f(x) = x \cdot sin(x) \cdot cos(x)$, determine $f'(x)$.
Given $f(x) = x \cdot sin(x) \cdot cos(x)$, determine $f'(x)$.
Flashcards
Derivative of a Constant
Derivative of a Constant
The derivative of a constant function is always zero.
Power Rule
Power Rule
The derivative of x^n is n*x^(n-1). Multiply by the exponent, reduce exponent by one.
Constant Multiple Rule
Constant Multiple Rule
The derivative of a constant times a function is the constant times the derivative of the function: d/dx [c * f(x)] = c * f'(x)
Definition of the Derivative
Definition of the Derivative
Signup and view all the flashcards
Tangent Line
Tangent Line
Signup and view all the flashcards
Secant Line
Secant Line
Signup and view all the flashcards
Derivative of Polynomials
Derivative of Polynomials
Signup and view all the flashcards
Derivative of Reciprocal Functions
Derivative of Reciprocal Functions
Signup and view all the flashcards
Derivative of Radical functions
Derivative of Radical functions
Signup and view all the flashcards
The Product Rule
The Product Rule
Signup and view all the flashcards
Study Notes
Derivatives of Functions
- The derivative of any constant is zero.
- A derivative is a function providing the slope at a given x-value.
- If f(x) = 8, its graph is a straight line at y = 8, having a slope of zero.
- The derivative of f(x), denoted as f'(x), equals zero in this case.
- The notation d/dx signifies differentiation with respect to x.
Power Rule
- The power rule helps find the derivative of monomials.
- Formula: d/dx (x^n) = n * x^(n-1), where n is a constant.
- Example: The derivative of x^2 using the power rule is 2 * x^(2-1) = 2x.
- The derivative of x^3 is 3x^2
- The derivative of x^4 is 4x^3
- The derivative of x^5 is 5x^4
Constant Multiple Rule
- The constant multiple rule helps find the derivative of a constant times a function.
- Formula: d/dx [c * f(x)] = c * f'(x), where c is a constant
- For 4x^7, bring the 4 to the front: 4 * d/dx (x^7) = 4 * 7x^6 = 28x^6
- The derivative of 8x^4 is 32x^3
- The derivative of 5x^6 is 30x^5
- The derivative of 9x^5 is 45x^4
- The derivative of 6x^7 is 42x^6
Definition of the Derivative
- An alternative way to find derivatives is the definition of the derivative.
- Formula: f'(x) = lim (h->0) [f(x+h) - f(x)] / h
- To find f(x+h), replace x with (x+h) in the original function.
- For f(x) = x^2, f(x+h) = (x+h)^2
- Expanding (x+h)^2 gives x^2 + 2xh + h^2
- Plugging into the formula: lim (h->0) [(x^2 + 2xh + h^2) - x^2] / h
- Simplify: lim (h->0) [2xh + h^2] / h
- Factor out h: lim (h->0) h(2x + h) / h
- Cancel h: lim (h->0) (2x + h)
- As h approaches zero, the result is 2x, confirming the power rule earlier.
Tangent and Secant Lines
- The derivative gives the slope of a tangent line at a specific x-value.
- A tangent line touches the curve at only one point.
- Example: For f(x) = x^2, f'(x) = 2x
- The slope of the tangent line at x = 1 is f'(1) = 2 * 1 = 2
- A secant line intersects the curve at two points.
- The slope of a secant line is calculated using two points: (y2 - y1) / (x2 - x1)
- As the two points of a secant line approach each other, the slope of the secant line approaches the slope of the tangent line.
- For f(x) = x^3, f'(x) = 3x^2
- The slope of the tangent line at x = 2 is f'(2) = 3 * 2^2 = 12
Polynomial functions
- Differentiate each monomial separately using the power rule.
- The derivative of x^3 + 7x^2 - 8x + 6 is 3x^2 + 14x - 8
- f'(x) of 4x^5 + 3x^4 + 9x - 7 is 20x^4 + 12x^3 + 9
- To find the slope of the tangent line at x = 2, plug in 2 into f'(x):
- If f(x) = 2x^5 + 5x^3 + 3x^2 + 4, then f'(x) = 10x^4 + 15x^2 + 6x
- f'(2) = 10(16) + 15(4) + 6(2) = 160 + 60 + 12 = 232
Rational Functions
- Rewrite the reciprocal as a negative power of x
- If f(x) = 1/x = x^(-1), rewrite the function as X = -1
- f'(x) = -1 * x^(-2) = -1 / x^2
- If f(x) = 1 / x^2, then f(x) = x^(-2)
- f'(x) = -2 * x^(-3) = -2 / x^3
- Rewrite the function as: f(x) = 8x^(-4)
- Then we can determine: f'(x) = -32x^(-5) = -32 / x^5
- Rewrite the function as: f(x) = x^(1/2)
- The derivative is f'(x) = (1/2) * x^(-1/2) = 1 / (2 * sqrt(x))
Radical Functions
- Rewrite with rational exponents and then use power rule:
- If f(x) = cuberoot(x^(5)) , then rewrite the function as x^(5-3)
- f'(x) = (5/3) * x^(2/3) = (5 * cuberoot(x^2)) / 3
- If f(x) = 7throot(x^(4)), then rewrite the function as x^(4/7)
- f'(x) = (4/7) * x^(-3/7) = 4 / (7 * 7throot(x^3))
Combining rules examples
- Distribute to begin:
- If: f(x) = x^2 * (x^3 + 7), find derivative of f(x) = x^5 + 7x^2
- Therefore is: f'(x) = 5x^4 + 14x
- Begin by expanding:
- f(x) = (2x - 3)^2=(2x - 3) * (2x - 3) = 4x^2 - 12x + 9 Then derivative is: f'(x) = 8x - 12
- Simplify:
- If f(x) = (x^5 + 6x^4 + 5x^3) / x^2 =x^3 + 6x^2 + 5x then f'(x) = 3x^2 + 12x + 5
Trigonometric functions
- The derivative of sin(x) is cos(x)
- The derivative of cos(x) is -sin(x)
- The derivative of sec(x) is sec(x)tan(x)
- The derivative of csc(x) is -csc(x)cot(x)
- The derivative of tan(x) is sec^2(x)
- The derivative of cot(x) is -csc^2(x)
The Product Rule
- Used when finding the derivative of the product of two functions.
- Formula: (f * g)' = f' * g + f * g'
- For x^2 * sin(x), let f = x^2 and g = sin(x)
- Then, f' = 2x and g' = cos(x)
- Thus: f' * g + f * g'= 2x * sin(x) + x^2 * cos(x)
- f = is 3x^4 + 7 and g is x^3 - 5x
- f' = 12x^3 and g' = 3x^2 - 5.
- Result: is 12x^3(x^3 - 5x) + (3x^4 + 7)(3x^2 - 5)
- Thus: f' * g + f * g'= 2x * sin(x) + x^2 * cos(x)
Challenge Product Rule Example
- Can find the derivative of multiple functions
- (f * g * h)' = f' * g * h + f * g' * h + f * g * h'
- For: f * g* h = (x^3)(tan(x))(3x^2 - 9), the result is: (3x^2) * tan(x) * (3x^2 - 9) + (x^3) * (sec^2(x)) * (3x^2 - 9) + (x^3) * (tan(x)) * (6x)
The Quotient Rule
- Used when finding the derivative of the quotient of two functions.
- (f/g)' = (gf' - fg') / g^2
- If: f = 5x + 6 , g = 3x - 7
- Therefore: f' = 5 , g' = 3 - 7
- Result: is ((3x - 7) * 5 - (5x + 6) * 3)
- Which can be simplified to ≈ -53 / (3x - 7)^2
- If: f = 5x + 6 , g = 3x - 7
Studying That Suits You
Use AI to generate personalized quizzes and flashcards to suit your learning preferences.
Description
Learn about derivatives of functions, including the derivative of a constant and the power rule. Also, learn how to find the derivative of a constant times a function using the constant multiple rule. Examples are provided.